2018
DOI: 10.3390/molecules23071659
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of the Traditional Herbal Formula Ukgansan and the In Vitro Antioxidant Activity of Ferulic Acid as an Active Compound

Abstract: Ukgansan (UGS), a traditional herbal formula composing seven medicinal herbal plants, has been applied in Asian countries for treating neurosis, insomnia, and irritability. Here, the current study performed a simultaneous determination of the seven marker compounds (liquiritin apioside, liquiritin, ferulic acid, glycyrrhizin, decursin, decursinol angelate, and atractylenolide I) using high-performance liquid chromatography (HPLC), to establish quality control of UGS. A 70% ethanol extract of UGS and a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Among the polyphenols found in goat's milk, gallic acid, chlorogenic acid, ferulic acid and catechins are the most abundant [10], which have demonstrated to have antioxidant properties [32][33][34], increase in energy expenditure in mice [35] and humans [36] and anti-inflammatory properties [37]. Thus, the polyphenol content in goat's milk could be directly responsible of the increase in energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Among the polyphenols found in goat's milk, gallic acid, chlorogenic acid, ferulic acid and catechins are the most abundant [10], which have demonstrated to have antioxidant properties [32][33][34], increase in energy expenditure in mice [35] and humans [36] and anti-inflammatory properties [37]. Thus, the polyphenol content in goat's milk could be directly responsible of the increase in energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified a few representative chemical compounds included in UGS using the analytical profile of high-performance liquid chromatography (HPLC) in which decursin, glycyrrhizin, and decursinol angelate were predominantly included 18 . Moreover, one of them, namely ferulic acid, shows antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UGS has been reported to improve behavioral deficits and protect neuronal cells from degeneration in animal models [20][21][22] . We also demonstrated that ferulic acid, one of the active compounds of UGS, could play an important role, as an antioxidant, in its therapeutic effects 18 . These previous reports strongly suggest that UGS could exert various therapeutic roles in the brain by targeting diverse cellular components.…”
mentioning
confidence: 80%
See 2 more Smart Citations